2022
DOI: 10.1177/19401612221143067
|View full text |Cite
|
Sign up to set email alerts
|

Just a “Mouthpiece of Biased Elites?” Populist Party Sympathizers and Trust in Czech Public Service Media

Abstract: Existing research indicates that people with populist attitudes express lower trust in media, especially in Public Service Media. It is assumed that these people are alienated because of their values: populist ideology stems from anti-pluralism whereas Public Service Media promotes pluralism. This study tests this assumption by comparing the predictors of trust in Public Service Media between the populist party sympathizers and the sympathizers of other political parties in the Czech Republic. Two main expecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…While there was a broad consensus for the expectations of PSM, participants differed significantly in their actual assessments of the extent to which PSM meets these expectations, similar to the findings of the study on quality journalism by Karlsson and Clerwall (2019). Interestingly, unlike previous research (Campos Rueda, 2023;Smejkal et al, 2022) we observed no discernible patterns of difference in the assessment (satisfaction or criticism) of PSM performance among participants who support populist and non-populist parties, and non-voters. However, it is important to note that this may be attributed to the qualitative nature of this study, which serves as a research probe without making any claims to representativity.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…While there was a broad consensus for the expectations of PSM, participants differed significantly in their actual assessments of the extent to which PSM meets these expectations, similar to the findings of the study on quality journalism by Karlsson and Clerwall (2019). Interestingly, unlike previous research (Campos Rueda, 2023;Smejkal et al, 2022) we observed no discernible patterns of difference in the assessment (satisfaction or criticism) of PSM performance among participants who support populist and non-populist parties, and non-voters. However, it is important to note that this may be attributed to the qualitative nature of this study, which serves as a research probe without making any claims to representativity.…”
Section: Discussionsupporting
confidence: 65%
“…The main criterion for recruiting participants was their political preference: two focus groups comprised of participants who voted for parties that could be described as populist in the preceding election; two focus groups consisted of people who voted for nonpopulist parties; and the remaining two groups were made up of non-voters. We employed the criterion of political preferences based on previous research (Smejkal et al, 2022), indicating differences in the reasons for trust between individuals who sympathize with populist parties and those who support other political parties. Consequently, this could mean that the expectations of the voters of populist and non-populist parties may vary.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation